180k views
1 vote
T: 3(t + 3) + 5(3 + 2t) – 76 = 0

2 Answers

4 votes
Expand the brackets
—That’ll be 3t + 9 + 15 + 10t - 76 = 0
Then we rearrange
3t + 10t = 13t
15+9-76 = - 52

Therefore , it’ll be 13t - 52 = 0
Take “-52” to the other side then it’ll turn to “ +52”

13t = 52

Divide both sides by 13

13t/13 = 52/13

T = 4

Simple
User Andrey Rudenko
by
6.2k points
5 votes

Answer:


\huge\boxed{\sf t = 4}

Explanation:


\sf 3(t+3)+5(3+2t)-76 = 0\\\\Expanding \ Parenthesis\\\\3t + 9 + 15 + 10t -76 = 0\\\\13t + 24 -76 = 0\\\\13t - 52 = 0\\\\Add \ 52 \ to \ both \ sides\\\\13t = 52\\\\Dividing\ both\ sides\ by\ 13\\\\t = 52/13\\\\t = 4\\\\\rule[225]{225}{2}

Hope this helped!

~AH1807

User Jaryl
by
5.3k points